COMPULSIVE BUYING BEHAVIOR PADA KONSUMEN RITEL FORMAT FASHION STORE - KURNIA, NATALISA INDAH (Kajian Ilmiah Mahasiswa Manajemen, 2013)
Everyone’s life is unavoidable from shopping habit especially in fashion things. There are so many fashion store now in Indonesia and all over the world, because fashion store offer goods that suitable with trend that growth. Consument habits in shopping is always different, there is some that shop something they need, but there is some that shop very extreem compare with other people and we said that as compulsive buying behavior. This paper discusses the phenomenon of compulsive buying behavior in which the writer wanted to know the causes, processes, and the impact of compulsive buying behavior in the consumer retail fashion store format in Surabaya. Compulsive buying behavior is affected by family, psychological, sociological, situational, and materialism, that cause someone do buy something uncontrolable. Compulsive buying behavior can have a negative effect for the consumer is to use all means in order to get the goods they want. Then it will broke someone relationship with the other and cause psychological and financial problem to the compulsive consument.